In the transition towards plant-based diets. The case of Sweden, Lithuania, Poland, Ukraine and Moldova - K Wendin; V Olsson; S Karkehabadi; M Knicky; M Korzeniowska; A Kabasinskiene; Z Miknienė; A Getya; M Matvieiev; N Hryshchenko; E Scripnic; L Caisin; et al. (Future Foods)
A diet rich in plant-based foods and lower in animal foods is associated with a lower impact on the environment and improved public health. However, not all consumers are willing to reduce meat consumption. A challenge is to understand consumer attitudes towards the reduction of meat consumption and the replacement of meat with plant-based analogues. The present study aimed to investigate the attitudes toward the consumption/production of meat analogues among consumers in Sweden, Poland, Lithuania, Ukraine and Moldova. The survey was conducted by an online questionnaire. Participants from Sweden, Lithuania and Poland were significantly (p < 0.05) more interested in eating meat analogues than participants from Ukraine and Moldova, although extreme particiants were found in all countries, from those scoring 0 to those scoring 100. Overall, the healthiness and tastiness of meat analogues were considered as important factors by the participants from all countries. The participants from all participating countries were mainly negative to the use of the word “meat” in the names of plant-based analogues, and suggestions for new names included the word “plant”. The results from the present study contribute to a better understanding of the barriers and drivers of the transition towards plant-based diets in Sweden, Lithuania, Poland, Ukraine and Moldova.